Neophobia and innovation in Critically Endangered Bali myna, Leucopsar rothschildi - Rachael Miller; Elias Garcia-Pelegrin; Emily Danby (Royal Society Open Science, 2022)
Behavioural flexibility can impact on adaptability and survival, particularly in today's changing world, and encompasses associated components like neophobia, e.g. responses to novelty, and innovation, e.g. problem-solving. Bali myna (Leucopsar rothschildi) are a Critically Endangered endemic species, which are a focus of active conservation efforts, including reintroductions. Gathering behavioural data can aid in improving and developing conservation strategies, like pre-release training and individual selection for release. In 22 captive Bali myna, we tested neophobia (novel object, novel food, control conditions), innovation (bark, cup, lid conditions) and individual repeatability of latency responses in both experiments. We found effects of condition and presence of heterospecifics, including longer latencies to touch familiar food in presence than absence of novel items, and between problem-solving tasks, as well as in the presence of non-competing heterospecifics than competing heterospecifics. Age influenced neophobia, with adults showing longer latencies than juveniles. Individuals were repeatable in latency responses: (1) temporally in both experiments; (2) contextually within the innovation experiment and between experiments, as well as being consistent in approach order across experiments, suggesting stable behaviour traits. These findings are an important starting point for developing conservation behaviour related strategies in Bali myna and other similarly threatened species.